2014
DOI: 10.1177/0954406214533527
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear elasto-plastic analysis of a sandwich cylindrical shell with core plasticity included

Abstract: In this paper, static response of a sandwich cylindrical shell under elasto-plastic deformation is investigated. The faces are made of some isotropic materials and the core is made of an orthotropic material both with linear work hardening behavior. The faces are modeled as thin cylindrical shells obeying the Kirchhoff-Love assumptions. The core material is modeled as a special orthotropic solid in which its in-plane stresses are assumed to be negligible. The Prandtl-Reuss plastic flow theory and von Mises yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Comprehensive reviews of various analytical and numerical studies of sandwich structures can be found in Noor et al., 4 Librescu and Hause, 5 Vinson, 6 and Altenbach 7 . Moreover, a review of some publications considering the elastic-plastic behavior of sandwich structures can be found in Kargarnovin and Shokrollahi 8 where Kargarnovin and Shokrollahi studied simply supported sandwich cylindrical shell panels, undergoing elastic-plastic deformation using Ritz method.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive reviews of various analytical and numerical studies of sandwich structures can be found in Noor et al., 4 Librescu and Hause, 5 Vinson, 6 and Altenbach 7 . Moreover, a review of some publications considering the elastic-plastic behavior of sandwich structures can be found in Kargarnovin and Shokrollahi 8 where Kargarnovin and Shokrollahi studied simply supported sandwich cylindrical shell panels, undergoing elastic-plastic deformation using Ritz method.…”
Section: Introductionmentioning
confidence: 99%